2013
DOI: 10.1242/jcs.123653
|View full text |Cite
|
Sign up to set email alerts
|

Promoter type influences transcriptional topography by targeting genes to distinct nucleoplasmic sites

Abstract: SummaryBoth the sequence of a promoter and the position of a gene in 3D nuclear space play crucial roles in gene regulation, but few studies address their inter-relationship. Using human and viral promoters on mini-chromosomes and RNA fluorescence in situ hybridization coupled to 'high-precision' localization, we show that promoters binding the same transcription factors and responding to the same signaling pathways tend to be co-transcribed in the same transcription factories. We go on to suggest how such spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…Therefore, these data argue neither in favor of nor against putative ''transcription factories'' as they are currently defined (Cook, 1999) but suggest that such factories may be dynamically assembled rather than immobile structures. A recent study revealed that sequences within the promoter might drive the colocalization between these NFkB-regulated genes (Larkin et al, 2013). Therefore, an alternative model might involve sequencespecific elements within the promoters that facilitate the accumulation of different thresholds of general transcription factors for the three genes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these data argue neither in favor of nor against putative ''transcription factories'' as they are currently defined (Cook, 1999) but suggest that such factories may be dynamically assembled rather than immobile structures. A recent study revealed that sequences within the promoter might drive the colocalization between these NFkB-regulated genes (Larkin et al, 2013). Therefore, an alternative model might involve sequencespecific elements within the promoters that facilitate the accumulation of different thresholds of general transcription factors for the three genes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that these preferences are a reflection of gene regulation by shared sets of transcription factors; a high frequency of clustering has been detected for genes regulated by both Klf1 and TNF-a (19,21). It also seems that promoter identity directs the coassociation preference (22). It is not clear how specialization of factories is achieved, but preferences may be established through self-organization principles, driven by the sharing of specific transcription factors (23).…”
Section: Introductionmentioning
confidence: 99%
“…When introduced into cells, mini‐chromosomes were recruited to specific foci within the nucleus in a promoter‐specific manner (Xu and Cook, ). Mini‐chromosomes carrying identical (intron‐less) transcription units were transcribed in the same factories, but those with intronic sequence were targeted to and transcribed in a different factory (Xu and Cook, ; Larkin et al, ). In support of this finding, ChIA‐PET experiments show that intron‐less genes often contact each other (Li et al, ).…”
Section: Transcriptional Microenvironments: Coming Together Keeping mentioning
confidence: 99%